الأخطاء التعبيرية عند تلاميذ السنة الرابعة متوسط للموسم الدراسي 2020/2021 بولاية الوادي مدارس مختارة - رابح, بريبش, حنان حليمة (University of El-oued, 2021)
الملخص:تعتبر اللغة العربية من أقدم لغات العالم، حيث شرفها الله سبحانه وحفظها بنزول القرآن الكريم بها , قال تعالى " وإنَّهُ لَتَنْزِيلُ رَبِّ العَالَمِينِ ◊ نَزَلَ بِهِ الرُوحُ الأمِينُ عَلَى قَلْبِكَ لِتَكُونَ مِنَ المُنْذِرِينَ بِلِسَانٍ عَرَبِيٍّ مُبِينٍ " الشعراء (195◊196) , لكن متلقي هذه اللغة يصادفون مشاكل أثناء تعلمها في عدة مجالات أبرزها التعبير الكتابي , إذ لاحظ الباحثون اللغويون و النحاة ضعفا في هذا المجال فقاموا بتقديم طرق فعالة تسهم في سلامة التعبير من الناحية الإملائية و الصرفية و التركيبية النحوية , فظاهرة الأخطاء التعبيرية لم يسلم منها المتعلم في جميع المراحل التعليمية المختلفة خاصة مرحلة الطور المتوسط وتوصلنا إلى عدة نتائج أهمها : - التعبير الكتابي وسيلة الإنسان لترجمة أفكاره فعندما يفكر يستخدم الألفاظ والجمل و التراكيب في كتابته للتعبير عما يجول في خاطره. - التعبير الكتابي أساس تدريس اللغة العربية فهو أساس عملية التواصل في جميع الميادين . - يتعرض المتعلمون إلى عدة أخطاء في التعبير الكتابي لاسيما في الجانب النحوي والصرفي والإملائي والتركيبي خاصة من حيث الإعراب من جانب النحو, والإبدال والحذف من الجانب الإملائي, والأسلوبي التعبيري في جوانب التركيب. - غلبت الأخطاء الإملائية على تعابير تلاميذ السنة الرابعة متوسط إذ شكّلت الأغلبية الساحقة وهذا راجع إلى قلة المطالعة . - يلعب المعلم دورا مهما في تحفيز التلاميذ على ترجمة أفكارهم وصياغتها في عبارات مقبولة وإخراج مكبوتاتهم . - لتفادي الأخطاء التعبيرية خاصة التركيبية والأسلوبية منها يجب على الأستاذ أن يستعمل اللغة الفصيحة فقط داخل القسم و ويفرضها أيضا على التلاميذ. - لتفادي الأخطاء التعبيرية في الطور المتوسط يجب تكوين التلاميذ تكوينا جيدا منذ المرحلة الابتدائية . - يجب تنمية المهارات اللغوية لدى التلاميذ من أجل إيجاد مساحة أكبر للتعبير عن أفكارهم . - تخصيص وقت كاف لمادة التعبير الكتابي من أجل تعويد التلاميذ على التعبير . - يجب على المعلم أن يشجع التلاميذ على أعمالهم التعبيرية وهذا من أجل زرع الثقة في أنفسهم . - يستحسن أن تكون المواضيع التعبيرية متوافقة مع سن المتعلمين ومستواهم المعرفي و العقلي و الوجداني. - إعطاء الحرية في بعض الأحيان للتلاميذ في اختيار موضوع التعبير من أجل إعطاء فرصة لإخراج مكتوباتهم. - لابد من تفعيل حصة المطالعة و إعطائها مساحة أكبر ووقت أطول في التعليم لأنها هي الأساس في تكوين الأفكار والاطلاع على مجالات الحياة المختلفة . - عدم تقيّد تلاميذ الرابعة متوسط بالمطلوب منهم في التعبير يعود لعدم فهمهم و استيعابهم للموضوع , أو لعدم دخول موضوع التعبير في اهتماماتهم . Abstract: The Arabic language is considered one of the oldest languages in the world, where God Almighty honored and preserved it by the revelation of the Noble Qur’an, the Almighty said: “And it is the revelation of the Lord of the worlds They encounter problems while learning in several areas, most notably written expression, as linguists and grammarians noticed a weakness in this area, so they presented effective methods that contribute to the integrity of expression in terms of spelling, morphology and grammatical structure. The phenomenon of expressive errors was not spared the learner in all the different educational stages. Especially the middle stage, and we reached several results, the most important of which are: Written expression is a human’s way of translating his thoughts. When he thinks, he uses words, sentences, and structures in his writing to express what is on his mind. Written expression is the basis for teaching the Arabic language, as it is the basis of the communication process in all fields. - Learners are exposed to several errors in written expression, especially in the grammatical, morphological, spelling and syntactic aspect, especially in terms of syntax in terms of syntax, substitution and deletion from the spelling aspect, and expressive stylistics in aspects of structure. - Spelling errors prevailed on the expressions of the fourth year intermediate students, as they constituted the overwhelming majority, and this is due to the lack of reading. The teacher plays an important role in motivating students to translate their ideas and formulate them in acceptable terms and to bring out their repressions. - To avoid expressive errors, especially structural and stylistic ones, the teacher must use the formal language only within the department and also impose it on the students. - To avoid expressive errors in the middle stage, students must be well formed from the primary stage. Students' language skills must be developed in order to create more space for expressing their ideas. Allocate sufficient time for written expression in order to accustom students to expression. - The teacher should encourage the students to express their actions and this is in order to instill confidence in themselves. It is desirable that the expressive topics be compatible with the age of the learners and their cognitive, mental and emotional level. Giving the students freedom sometimes to choose the topic of expression in order to give an opportunity to produce their writings. - It is necessary to activate the reading share and give it more space and more time in education because it is the basis for forming ideas and learning about different areas of life. The fourth average pupils’ failure to comply with what is required of them in expression is due to their lack of understanding and understanding of the subject, or because the subject of expression did not enter their interests.
Keywords: الأخطاء التعبيرية / الرابعة متوسط /ولاية الوادي /مدارس مختارة: Expressive errors / fourth average / Valley State / selected schools